Determinants of Cash Holding in The Jakarta Islamic Index: The Role of Net Working Capital, Cash Flow, and Capital Expenditure - Handreyan Handreyan; Yusnita Octafilia; Willy Andresen; Dhoni Rizky Widya Mahardika (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to determine the influence of Net Working Capital, Cash Flow and Capital Expenditure on Cash Holding. The object of this research is the Jakarta Islamic Index (JII) company listed on the IDX for the period of 2016 to 2020. The population in this study is 30 companies. The sampling technique in this study used the purposive sampling method and obtained a sample of 29 companies that were used as research samples. The data analysis technique used was multiple linear regression analysis using the Software Statistical Package for the Social Sciences (SPSS) application. The results of this study show that the variables of Net Working Capital, Cash Flow and Capital Expenditure do not have a significant effect on Cash Holding of Jakarta Islamic Index (JII) companies listed on the IDX from 2016 to 2020.